2022
DOI: 10.3390/biom12121891
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Overload and Mitochondrial Metabolism

Lauren L. Walkon,
Jasiel O. Strubbe-Rivera,
Jason N. Bazil

Abstract: Mitochondria calcium is a double-edged sword. While low levels of calcium are essential to maintain optimal rates of ATP production, extreme levels of calcium overcoming the mitochondrial calcium retention capacity leads to loss of mitochondrial function. In moderate amounts, however, ATP synthesis rates are inhibited in a calcium-titratable manner. While the consequences of extreme calcium overload are well-known, the effects on mitochondrial function in the moderately loaded range remain enigmatic. These obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…The calcium in mitochondria is a double-edged sword. Although low levels of calcium are crucial for maintaining most excellent ATP production speed rates, overcoming the extreme levels of mitochondrial calcium retention can lead to mitochondrial dysfunction [ 55 ]. So far, few studies have reported on the effects of VK2 on calcium homeostasis regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium in mitochondria is a double-edged sword. Although low levels of calcium are crucial for maintaining most excellent ATP production speed rates, overcoming the extreme levels of mitochondrial calcium retention can lead to mitochondrial dysfunction [ 55 ]. So far, few studies have reported on the effects of VK2 on calcium homeostasis regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the calcium balance system under stress causes its disordered distribution and overload, leading to functional abnormalities. 41 Mitochondrial calcium overload can promote mROS production, leading to the opening of the mitochondrial permeability transition pore, release of cytochrome C, and apoptosis. 42 Multiple studies have reported the important role of ER-mitochondria Ca2+ signals in regulating cell death in various animal models.…”
Section: Discussionmentioning
confidence: 99%
“…4 Excessive accumulation of free Ca 2+ in the cytoplasm, referred to as "calcium overload", may cause mitochondrial dysfunction and cell death. 5 Overloaded Ca 2+ disrupts mitochondrial calcium homeostasis, upregulates caspase 3, and induces cell apoptosis. It is important to note that cancer cells are more susceptible to Ca 2+ overload than normal cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ca 2+ is the second messenger in cells and has a significant impact on cell proliferation, apoptosis, migration, and gene expression . Excessive accumulation of free Ca 2+ in the cytoplasm, referred to as “calcium overload”, may cause mitochondrial dysfunction and cell death . Overloaded Ca 2+ disrupts mitochondrial calcium homeostasis, upregulates caspase 3, and induces cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%